Creating shared value and sport employees' job performance: the mediating effect of work engagement. Issue 2 (4th March 2022) - Wu, Ji; Inoue, Yuhei; Filo, Kevin; Sato, Mikihiro
ABSTRACT: Research question: The salience of creating shared value (CSV) in innovating the process of social change has been acknowledged; however, we know little about CSV from views of employees who create shared value. This study examined how employees of a sport organization perceive their organization's CSV, and assessed the connections between employee CSV perception, vision integration, work engagement, and job performance. Research methods: A new scale of employee CSV perception was validated using data from 207 employees within a sport organization in China. Structural equation modeling was performed, with a separate sample of 181 employees, to test the hypothesized relationships. The data were obtained through web-based questionnaires. Results and findings: Employee CSV perception – formed as a second-order factor including sport, social, and economic values – was positively associated with vision integration. Subsequently, vision integration had a positive relationship with in-role behavior (i.e. a measure of job performance), and this relationship was mediated by work engagement. Implications: This study advances a theoretical understanding of CSV from the employees' perspective. Findings suggest that a sport organization can use CSV to increase employees' adoption of its vision, work engagement, and in-role behavior through team-building activities that facilitate employees' understanding of the vision.